Spatial and temporal pattern of rice domestication during the early Holocene in the lower Yangtze region, China - Huan, Xiujia; Lu, Houyuan; Jiang, Leping; Zuo, Xinxin; He, Keyang; Zhang, Jianping (Holocene (Sevenoaks), 2021)
Rice is among the world’s most important and ancient domesticated crops. However, the spatial and temporal pattern of the early rice domestication process remains unclear due to the lack of systematic study of wild/domesticated rice remains and corresponding dates during the early Holocene. Here, we collected 248 samples from five typical Shangshan cultural sites in the lower Yangtze region where is the most likely origin place of rice for phytolith analysis. The results showed the following. (1) Rice bulliform phytoliths from the five sites all present domestication traits, suggesting that the rice domestication process had begun across the region by the early stage of the Holocene. (2) The relative domestication rates reflected by the rice bulliform phytoliths were different between sites, the sites with higher domestication rates were distributed closer to the mainstream river. (3) The rice domestication process revealed by bulliform phytoliths can be divided into three periods during the early Holocene: from 10 to 9 ka, rice domestication began and stayed at a low level under 35%; from 9 to 8.5 ka, rice domestication level increased to 50%; and from 8.5 to 8 ka, rice domestication level was in a fluctuating state. (4) By 9 ka BP, rice double-peaked phytoliths from glume cells are present in most of the studied sites, which imply the presence of crop dehusking processing. This study reconstructed the spatial and temporal patterns of rice domestication during the early Holocene, which will improve our knowledge of early crop domestication and enhance our understanding of changes in rice status.